KEBUDAYAAN LOKAL SEBAGAI SUMBER INSPIRASI (Tinjauan Antropologi Visual pada Pelukis di Kota Makassar) - Karta Jayadi (Gelar : Jurnal Seni Budaya, 2014)
The article talks about local culture in South Sulawesi as the inspiration source for the painters in Makassarin visual anthropology point of view. The local culture consists of material as well as non material cultureincluding Perahu Pinisi (Pinisi Boat), Baju Bodo,Aksara (Bodo Aksara Dress), Mythos and legend, and alsoPesona Alam (the beauty of nature). The culture is expressed in the work of representational as well as nonrepresentationalpainting. The visual anthropology analysis is used to help understanding the phenomena ofâ€œnew visualâ€ presented by the painters as an effort to present the new element and form of the imaged localculture. The form of representational work can be seen in the cultural themes such as Perahu Pinisi, BajuBodo, and Pesona Alam. The work also presents the complete and proportional visual elements so thatcultural objects can be photographically imagined even in different situation. For the reason, the closerelationship between the inspiring local culture and the inspired painting symbolically has an equal value,while non-representational work is imaginatively described by the painter. The visual values are illustratedbased on aesthetic fiction, experience, and the deep information from alphabet, mythos, and legend. In thispainting, the painter has different interpretation in visualize the information in case of form, color, andcomposition. Thus, the imagination and reality of culture cannot be separated from the ownerâ€™s community sothat it will always appear as the new identity and personality through the new visualization product.Keywords: culture, local, inspiration, anthropology, visual